2020
DOI: 10.3390/ijerph17176027
|View full text |Cite
|
Sign up to set email alerts
|

Clearing the Smoke Screen: Smoking, Alcohol Consumption, and Stress Management Techniques among Canadian Long-Term Care Workers

Abstract: Background: Currently, there is abundant research indicating that smoking and alcohol consumption have significant impacts on morbidity and mortality, though little is known about these behaviors among Canadian health care workers. The objective of this study was to examine health and coping behaviors, such as smoking and alcohol consumption as well as stress management techniques, among health care workers consisting of gendered, racialized, and immigrant employees. Methods: Drawing on a single-case, mixed-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The emotional demands of managing one's own emotions as well as those of others can have a negative influence on healthcare professionals' health, wellbeing and job performance, leading to high levels of stress and burnout [73,74]. Long-term care workers prefer coping strategies such as mindfulness, meditation and solitary recreation, as well as drawing on social support, as a sources of stress relief [75]. It has been shown that practicing mindfulness reduces professionals' emotional overload and burnout, while also enhancing positive cognitive retraining [37].…”
Section: Discussionmentioning
confidence: 99%
“…The emotional demands of managing one's own emotions as well as those of others can have a negative influence on healthcare professionals' health, wellbeing and job performance, leading to high levels of stress and burnout [73,74]. Long-term care workers prefer coping strategies such as mindfulness, meditation and solitary recreation, as well as drawing on social support, as a sources of stress relief [75]. It has been shown that practicing mindfulness reduces professionals' emotional overload and burnout, while also enhancing positive cognitive retraining [37].…”
Section: Discussionmentioning
confidence: 99%
“…As has been revealed, chronic stress is positively correlated with interleukin production and eosinophil counts, which implicates the inflammatory process in asthma, while higher family savings contribute to reducing interleukin production and eosinophil counts [ 91 ]. Moreover, stress can promote tobacco use [ 92 ], and, compared with males, females are more likely to smoke when managing stress [ 93 ]. However, household income is negatively related to nicotine dependence and chronic stress, and it can moderate the positive relationship between stress and smoking [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…More research should be devoted to understanding differences in quitline effectiveness for individuals who do and do not have mental health conditions, as well as how the extent of quitline services offered might impact these disparities. Further, more work should be done to understand the potential impact of quitlines on smoking disparities between immigrant and non-immigrant populations, as several studies have highlighted differences in smoking by immigration status, the country from which an individual immigrates, and male–female differences within groups of individuals who have immigrated, though findings as to the direction of these disparities have varied across studies [ 48 , 49 ]. Additionally, our study did not factor in the extent to which quitlines were advertised, nor how media campaigns might have influenced reach or cessation.…”
Section: Discussionmentioning
confidence: 99%